Strategi Bauran Pemasaran Produk Real Estate Di PT Mitra Karya Makmur Jaya Tulungagung - Mohammad Saiful Rifai; Sri Wahyuni Mega Hastuti; Ahsin Daroini (Universitas Islam Kadiri, 2022)
The purpose of this research is to find out the application of marketing mix strategies at PT Mitra Karya Makmur Jaya as well as to find out its SWOT analysis. The approach used is a phenomenological approach with a type of field research using descriptive qualitative methods. The results showed that the implementation of the marketing mix strategy carried out by PT Mitra Karya Makmur Jaya was Product, product concept following market trends, good quality, providing warranty, products in the form of soil and buildings, there is a choice of types, and provide solutions for consumer desires. Price, price according to quality, ease of payment system, and reduce the selling price by not providing discounts. Place, legal and strategic location, and has special criteria. Promotion, advertising using brochures, billboards, and social media, through marketing that stands by in the marketing office. Process, product through ordering, fast process, clear and organized flow. People, interesting and informative services, competent employees and have a linear educational background, employee training, There are sales targets. Physical Evidence, there are roads, street lighting, drainage, parks, musholla and playground, decent facilities, public facilities built before launching, and social facilities are built as the project progresses. Based on a SWOT analysis conducted that PT Mitra Karya Makmur Jaya is in quadrant II which means the strategy used is a difersification strategy. The strategy that can be done by the company is to subtitute materials, minimize development process errors to minimize production costs. The quality of the building must be maintained as a plus value of the company. Improving marketing services, facilitate the flow of ordering products, as well as pay attention to the difference in selling prices with competitors.